Hydrofold technology: Terminal year end report - Abellera, Marie Ysabelle Dimayuga (Animo Repository, 2022)
HydroFold Technology is a corporation founded and managed by the following incorporators, namely, Marie Ysabelle Abellera, Healthlyn Gaw, Dominic Laohoo, Jamie Cristle Tchoi and Earl Kennard Uy. As entrepreneurs of the 21st century, these individuals want to initiate change and take initiative that is good for both the people and the planet. The rise of single use plastic disposals in landfills, rivers and oceans, can greatly harm the environment as it takes thousands of years to decompose. Although people are now slowly shifting to a more eco-friendly and sustainable lifestyle, some consumers today are still not willing to bring their own reusables due to the inconvenience tied to it such as being heavy and bulky, even if the contents are already empty. Hence, with the problem of the disposal of single use plastics, the demand for eco-friendly and sustainable products, and inconvenience of bringing water bottles, the founders took this opportunity for them to make a change in this world through their business. Hydrofold Technology’s objective is to provide innovative, quality, and convenient products for customers as well as to promote sustainability through building long-term relationships with employees and customers. The incorporators themselves personally want to contribute to a zero waste lifestyle by bringing their own reusable water bottles but at the same time experiencing the inconvenience of it due to its weight and size. With that being said, they have thought of a product that could help solve this problem, which is HydroFold Technology's collapsible water bottle. This product is environmentally friendly, sustainable, and practical which will meet the current demands of the consumers of today. With the combined knowledge, skills, and strengths of each founder, they envision establishing a company that will be a catalyst for change in the industry. Hydrofold has accomplished its goal of providing innovative, quality, and convenient collapsible water bottles to their customers through content creation, social media marketing, and the use of various distribution channels to reach their customers. Hydrofold was able to build meaningful relationships with its customers and suppliers. Moreover, the company reached the target number of units to produce which is 250 units and all of which were sold. Hydrofold was also able to conduct its planned Human resources activities which include CSR activities, monthly meetings, and team building activities. After the operating period for Hydrofold Technology, the company was able to build the brand, serve its customers and attain its financial objectives. Hydrofold Technology generated gross sales amounting to Php 117,800 and achieved an ROI of 97.96%. Keywords : Water Bottle, Plastic Pollution, Sustainability , Single-Used Plastics, Zero Waste Lifestyle